2006
DOI: 10.1007/s10286-006-0276-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrogenic cardiac arrhythmias:

Abstract: Perspective■ Evidence for sympathetic upregulation as a mechanism for cerebral influences on cardiac structure and function In 1913 Goodman Levy [24, 25] showed that chloroforminduced ventricular tachyarrhythmias were abolished by cardiac sympathetic denervation. Additionally, sympathetic activation induced identical ventricular tachyarrhythmias, indicating a direct neurological rather than cardiac effect of chloroform. Subsequently, Beattie [3] showed that these tachyarrhythmias were abolished by mid-collicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(76 citation statements)
references
References 51 publications
(53 reference statements)
1
72
0
3
Order By: Relevance
“…ECG abnormalities, including atrial arrhythmia, have been reported in patients with no underlying cardiac disease [19,20]. Moreover, some studies have reported a significantly higher incidence of atrial tachyarrhythmia, particularly in patients with anterior circulation infarction [21]. …”
Section: Discussionmentioning
confidence: 99%
“…ECG abnormalities, including atrial arrhythmia, have been reported in patients with no underlying cardiac disease [19,20]. Moreover, some studies have reported a significantly higher incidence of atrial tachyarrhythmia, particularly in patients with anterior circulation infarction [21]. …”
Section: Discussionmentioning
confidence: 99%
“…14, 15 The efficacy of ART such as cardiac afferent denervation after myocardial infarction 16 and sympathectomy to treat ventricular tachycardia (VT) storm could be due to a reduction of these conflicts between levels of the cardiac nervous system. 17, 18 In these settings it is very likely that the intrinsic nervous system of the heart is able to provide the neural coordination and ensure electrical stability without the interference of central input.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The locus coeruleus provides adrenergic innervation and important components of arousal and attention selection (Aston-Jones & Cohen 2005), while the raphé, in addition to its mood and temperature roles, also assists in modulation of upper airway muscle tone (Kubin et al 1992). The medullary injury in OSA and CCHS is principally unilateral, which poses unique concerns for conditions of high sympathetic tone, since asymmetric sympathetic drive predisposes to certain forms of cardiac arrhythmia (Oppenheimer 2006). …”
Section: Pons and Medullamentioning
confidence: 99%